Mixed-Methods Evaluation of Real-Time Safety Reporting by Hospitalized Patients and Their Care Partners: The MySafeCare Application. Issue 2 (June 2020) - Collins, Sarah A.; Couture, Brittany; Smith, Ann DeBord; Gershanik, Esteban; Lilley, Elizabeth; Chang, Frank; Yoon, Cathy; Lipsitz, Stuart; Sheikh, Aziz; Benneyan, James; Bates, David W.
Abstract : Objective: The aims of the study were to evaluate the amount and content of data patients and care partners reported using a real-time electronic safety tool compared with other reporting mechanisms and to understand their perspectives on safety concerns and reporting in the hospital. Methods: This study used mixed methods including 20-month preimplementation and postimplementation trial evaluating MySafeCare, a web-based application, which allows hospitalized patients/care partners to report safety concerns in real time. The study compared MySafeCare submission rates for three hospital units (oncology acute care, vascular intermediate care, medical intensive care) with submissions rates of Patient Family Relations (PFR) Department, a hospital service to address patient/family concerns. The study used triangulation of quantitative data with thematic analysis of safety concern submissions and patient/care partner interviews to understand submission content and perspectives on safety reporting. Results: Thirty-two MySafeCare submissions were received with an average rate of 1.7 submissions per 1000 patient-days and a range of 0.3 to 4.8 submissions per 1000 patient-days across all units, indicating notable variation between units. MySafeCare submission rates were significantly higher than PFR submission rates during the postintervention period on the vascular unit (4.3 [95% confidence interval = 2.8–6.5] versus 1.5 [95% confidence interval = 0.7–3.1], Poisson) ( P = 0.01). Overall trends indicated a decrease in PFR submissions after MySafeCare implementation. Triangulated data indicated patients preferred to report anonymously and did not want concerns submitted directly to their care team. Conclusions: MySafeCare evaluation confirmed the potential value of providing an electronic, anonymous reporting tool in the hospital to capture safety concerns in real time. Such applications should be tested further as part of patient safety programs.